The Battle for the Falklands - Hastings, Max and Jenkins, Simon (London Book Club Associates, 1983)
A combination of on-the-spot reporting and an analysis of the political and diplomatic developments traces the curious course and far-reaching effects of the Falkland Islands War.
Include Pictures, Appendix and Index
Keywords: Falkland Islands War, 1982 -- Conflit des Malouines, 1982 -- Falkland-oorlog.